7. Franz Joseph Strauss, a Joachim of the Horn - Gîscă Petrea (Sciendo, 2022)
Franz Joseph Strauss was one of the brightest horns of the 19th century. He was born in Germany and worked all his life in Munich, being a first - horn player, composer, conductor and teacher. As a composer he wrote two concerts for horn and orchestra and several pieces for horn and piano, most of them, the author singing them in the first absolute audition. As a teacher, he participated in the creation of a German horn school, and his studies for natural horn are still valid today. Difficult and sometimes misunderstood by musicians of the time, Franz Strauss remains a landmark in the history of the horn and a legend in the art of horn performance.